Role of BET Proteins in Inflammation and CNS Diseases - Liu, Lei; Yang, Changjun; Candelario-Jalil, Eduardo (Frontiers in Molecular Biosciences, 2021)
Bromodomain and extra-terminal domain (BET) proteins consist of four mammalian members (BRD2, BRD3, BRD4, and BRDT), which play a pivotal role in the transcriptional regulation of the inflammatory response. Dysregulated inflammation is a key pathological process in various CNS disorders through multiple mechanisms, including NF-κB and Nrf2 pathways, two well-known master regulators of inflammation. A better mechanistic understanding of the BET proteins’ role in regulating the inflammatory process is of great significance since it could reveal novel therapeutic targets to reduce neuroinflammation associated with many CNS diseases. In this minireview, we first outline the structural features of BET proteins and summarize genetic and pharmacological approaches for BET inhibition, including novel strategies using proteolysis-targeting chimeras (PROTACs). We emphasize in vitro and in vivo evidence of the interplay between BET proteins and NF-κB and Nrf2 signaling pathways. Finally, we summarize recent studies showing that BET proteins are essential regulators of inflammation and neuropathology in various CNS diseases.